Robust cooperative output regulation of uncertain linear multi-agent systems not detectable by regulated output - Wang, Lei (2021)
This paper considers the robust cooperative output regulation problem via measurement feedback for a class of linear multi-agent systems, which is not detectable by regulated output. To solve it, necessarily additional measurement is assumed to be available, and the normal form defined on the additional measurement is utilized. Under mild assumptions on the communication network and the zero dynamics, a novel distributed measurement feedback controller can be established, consisting of the distributed dynamical compensator, internal model and possibly asymptotic observer, such that all regulated errors can globally exponentially converge to zero. Only regulated output of each agent needs to be transmitted to its neighbors, while neither the plant state nor the controller state is required to be exchanged with its neighbors.